The COVID-19 pandemic and subjective well-being: longitudinal evidence on satisfaction with work and family. (19th February 2021) - Möhring, Katja; Naumann, Elias; Reifenscheid, Maximiliane; Wenz, Alexander; Rettig, Tobias; Krieger, Ulrich; Friedel, Sabine; Finkel, Marina; Cornesse, Carina; Blom, Annelies G.
ABSTRACT: This paper provides a timely evaluation of whether the main COVID-19 lockdown policies – remote work, short-time work and closure of schools and childcare – have an immediate effect on the German population in terms of changes in satisfaction with work and family life. Relying on individual level panel data collected before and during the lockdown, we examine (1) how family satisfaction and work satisfaction of individuals have changed over the lockdown period, and (2) how lockdown-driven changes in the labour market situation (i.e. working remotely and being sent on short-time work) have affected satisfactions. We apply first-difference regressions for mothers, fathers, and persons without children. Our results show a general decrease in family satisfaction. We also find an overall decline in work satisfaction which is most pronounced for mothers and those without children who have to switch to short-time work. In contrast, fathers' well-being is less affected negatively and their family satisfaction even increased after changing to short-time work. We conclude that while the lockdown circumstances generally have a negative effect on the satisfaction with work and family of individuals in Germany, effects differ between childless persons, mothers, and fathers with the latter being least negatively affected.